Regulation of Microbial Metabolic Rates Using CRISPR Interference With Expanded PAM Sequences - Kim, Bumjoon; Kim, Hyun Ju; Lee, Sang Jun (Frontiers in Microbiology, 2020)
Genome-editing CRISPR/Cas9 technology has led to the development of artificial transcriptional repressors, also known as CRISPR interference (CRISPRi). The deactivated Cas9 (dCas9) protein guided by crRNA can specifically bind to target DNA sequences, including promoters and operators, without DNA cleavage. Protospacer adjacent motif (PAM) sequence dependence may be disadvantageous in the design of target-specific CRISPRi, as the PAM sequence is essential for DNA cleavage by the CRISPR/Cas9 system. We constructed a chromosomally integrated dCas9 system (araBAD::dcas9) in Escherichia coli under the control of the L-arabinose-inducible PBAD promoter. Plasmids carrying various crRNAs with target sequences specific for the gal promoter (-10 region), and the galETK structural genes in the gal operon, were transformed into dCas9-expressing E. coli. Cellular growth and/or galactose metabolic rates were monitored in the presence or absence of gratuitous L-arabinose. D-galactose consumption and cell growth rates were partially retarded by targeting transcriptional elongation but were fully inhibited by targeting transcriptional initiation. Moreover, RT-qPCR analysis showed that CRISPRi with several modified PAM sequences can repress the transcription of target DNAs. These results indicate that cellular metabolic rates and cell growth can be controlled by targeting structural genes or regulatory regions using CRISPRi; also, a loose PAM sequence dependence can expand the DNA targets of CRISPRi.